Cr3+‐Doped Sc‐Based Fluoride Enabling Highly Efficient Near Infrared Luminescence: A Case Study of K2NaScF6:Cr3+. Issue 2 (23rd December 2020) - Song, Enhai; Ming, Hong; Zhou, Yayun; He, Fanquan; Wu, Jiachang; Xia, Zhiguo; Zhang, Qinyuan
Abstract: The development of highly efficient and thermally stable broadband near‐infrared (NIR) luminescence materials is a great challenge to advance the next‐generation smart NIR light source. Benefitting from the low phonon energy and relatively weak electron phonon coupling effect of the fluoride, K2 NaScF6 :Cr 3+ phosphor is designed and obtained, which demonstrates a full width at half maximum of 100 nm peaking at ≈765 nm. Upon blue light excitation, the phosphor exhibits a high quantum efficiency of 74% and its emission intensity at 150 °C can keep 89.6% of the initial value at 25 °C. An NIR output power of 159.72 mW (input electric power, 1094 mW) with a high photoelectric conversion efficiency of ≈14.60%, light‐emitting diode (LED) device is presented based on this K2 NaScF6 :Cr 3+ phosphor. Furthermore, applying the high‐power NIR phosphor‐converted LED device as lighting source, clear and quick veins imaging and recognition in fingers, palm, wrist, and arm of the human hand are first realized, suggesting K2 NaScF6 :Cr 3+ phosphor has high promise in practical applications. Abstract : A highly efficient near‐infrared (NIR) emission fluoride phosphor K2 NaScF6 :Cr 3+ is discovered, and the origin of the excellent optical properties is demonstrated. Based on this phosphor, a light‐emitting diode device with an NIR output power of 159.72 mW and high photoelectric conversion efficiency of ≈14.60% is further presented, showing high potential for veins imaging.